Intravitreal Ampicillin Sodium for Antibiotic-Resistant Endophthalmitis: Streptococcus uberis First Human Intraocular Infection Report. (6th July 2010) - Velez-Montoya, Raul; Rascón-Vargas, Dulce; Mieler, William F.; Fromow-Guerra, Jans; Morales-Cantón, Virgilio
Abstract : Purpose . To describe the clinical characteristics, diagnosis, and treatment with intravitreal ampicillin sodium of a postoperative endophthalmitis case due to Streptococcus uberis ; an environmental pathogen commonly seen in mastitis cases of lactating cows. Methods . Case Report. A 52-year-old, Hispanic diabetic patient who suddenly developed severe pain and severe loss of vision, following vitrectomy. Results . The patient was diagnosed with postoperative endophthalmitis secondary to a highly resistant strain of Streptococcus uberis that did not respond to intravitreal antibiotics. He was treated with an air-fluid interchange, anterior chamber washout, intravitreal ampicillin sodium (5 mg/0.1 mL), and silicon oil tamponade (5000 ck). The eye was anatomically stabilized, though there was no functional recovery. Conclusion . Streptococcus uberis is an uncommon pathogen to the human eye, which has unique features that help the strain in developing resistance to antibiotics. While treatment with intravitreal ampicillin is feasible, there are still concerns about its possible toxicity.